2017
DOI: 10.1026/0049-8637/a000162
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Childcare Quality for Behavioral Adjustment in 3- to 5-Year-Old Children

Abstract: Abstract. This study examined the role of childcare process quality regarding the relation between family risks and preschoolers’ social–emotional problems. The study included 24 childcare centers with 42 groups in the German-speaking part of Switzerland. The 162 children in the sample were aged 3 – 5 years. Parents and teachers completed the Strengths and Difficulties Questionnaire (SDQ-Deu). Eight family risk factors were subsumed into a cumulative risk index. Childcare process quality was assessed by variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…To our knowledge, four other studies exist. Three found that center-based care was related to more externalizing but not internalizing problems [57][58][59]. A fourth study focused on motor, cognitive, language, and social skills but did not measure problem behavior.…”
Section: External Childcare In Switzerlandmentioning
confidence: 99%
“…To our knowledge, four other studies exist. Three found that center-based care was related to more externalizing but not internalizing problems [57][58][59]. A fourth study focused on motor, cognitive, language, and social skills but did not measure problem behavior.…”
Section: External Childcare In Switzerlandmentioning
confidence: 99%
“…The present study was part of the project "Long-term effects of early family risk on children's maladjustment and self-efficacy: individual, familial and extra-familial protective processes" (2016-2019) that belongs to the project "Promoting early learning and resilience through a strengthening learning dialogue -A project for promotion and professionalization of early childhood education in Swiss childcare centers" (2009-2012) (Wustmann Seiler et al, 2017). The study encompasses three measurement waves, from early childhood to middle school age.…”
Section: Participantsmentioning
confidence: 99%
“…Grund dafür sind schützende, risikomildernde Faktoren, die nach Rutter (1990) die Auftretenswahrscheinlichkeit psychischer Störungen senken oder die Auftretenswahr-scheinlichkeit einer positiven Entwicklung erhöhen. Ein Schutzfaktor kann dabei gleichzeitig promotiv (entwicklungsförderlich) und protektiv (schützend) sein oder sich nur als promotiv beziehungsweise nur als protektiv erweisen (Burke, Sticca & Perren, 2017;Scheithauer & Petermann, 1999;Masten & Barnes, 2018;Rutter, 1990;Wustmann Seiler, Müller & Simoni, 2017). Untersuchungen auf der Basis der interpersonalen Theorie von Sullivan (1953) belegen, dass eine hohe Freundschaftsqualität zum besten Freund beziehungsweise zur besten Freundin ein promotives und protektives soziales Unterstützungssystem bei vorhandenen elterlichen Belastungen sein kann (Lansford, Criss, Pettit, Dodge & Bates, 2003).…”
Section: Erziehungsbezogene Elterliche Depressivität Und Selbstwirksamkeitserwartung Von Kindern: Die Rolle Von Freundschaftsqualitätunclassified